Exenatide (Byetta) as a novel treatment option for type 2 diabetes mellitus - Bond, Aaron (Baylor Health Care System, 2006)
Exenatide is the first drug in the incretin mimetic class and is indicated for treatment of type 2 diabetes mellitus. Although structurally similar to the native glucagon-like peptide, this synthetic form has a much longer duration of action. Randomized trials have shown exenatide to be efficacious in improving glycemic control when combined with either metformin or a sulfonylurea. The dose is initially 5 mcg subcutaneously twice daily and may be titrated to 10 mcg subcutaneously twice daily to achieve better diabetes management. Nausea, vomiting, and diarrhea were the most common adverse events reported with exenatide therapy. Exenatide is not associated with hypoglycemia, which may provide advantages over adding insulin to a sulfonylurea or metformin.